2016
DOI: 10.1371/journal.pbio.1002360
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Global Health by Improving the Science of Scale-Up

Abstract: In its report Global Health 2035, the Commission on Investing in Health proposed that health investments can reduce mortality in nearly all low- and middle-income countries to very low levels, thereby averting 10 million deaths per year from 2035 onward. Many of these gains could be achieved through scale-up of existing technologies and health services. A key instrument to close this gap is policy and implementation research (PIR) that aims to produce generalizable evidence on what works to implement successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 31 publications
0
48
0
2
Order By: Relevance
“…The PC101 management tool is correctly seen as a means of overcoming the “silo” approach to individual disease management in which recommendations for different conditions may vary and even conflict and, more importantly, ensures that NCDs and mental health are not overlooked because of prioritisation of communicable diseases. For us, as researchers who look to rigorous research methods to guide health system development, this has been a powerful lesson in understanding that evidence of effectiveness is only one element under consideration by decision-makers [63]. Given clinicians’ strong attraction to the ease of integrating PC101 into clinic practice and the positive system effects of our intervention mentioned above, it might have been more useful to focus our primary analysis on lack of harm.…”
Section: Discussionmentioning
confidence: 99%
“…The PC101 management tool is correctly seen as a means of overcoming the “silo” approach to individual disease management in which recommendations for different conditions may vary and even conflict and, more importantly, ensures that NCDs and mental health are not overlooked because of prioritisation of communicable diseases. For us, as researchers who look to rigorous research methods to guide health system development, this has been a powerful lesson in understanding that evidence of effectiveness is only one element under consideration by decision-makers [63]. Given clinicians’ strong attraction to the ease of integrating PC101 into clinic practice and the positive system effects of our intervention mentioned above, it might have been more useful to focus our primary analysis on lack of harm.…”
Section: Discussionmentioning
confidence: 99%
“…32 There remains limited evidence understanding how best to do this, particularly in the context of a technical capacity gap in national planning and implementing bodies in many high burden countries. 50 This gap in delivery capacity has been demonstrated in other parallel programs, for example, the IMCI strategy, which was launched by the WHO in 1996. A multicountry evaluation conducted in Bangladesh, Brazil, Peru, Tanzania, and Uganda found that the WHO expected IMCI would be implemented fully regardless of the strength of the health system, and this assumption did not hold true.…”
Section: Lessons Learned For Dimension 2: Taking Interventions To Scalementioning
confidence: 99%
“…Similar to many low income countries, health care often fails at the point of deliverydespite laudable policy commitments [53]. The right to health is enshrined in the many national laws and regional and international treaties which Mozambique is party.…”
Section: Discussionmentioning
confidence: 99%